Design and Development of a Web-Based Laundry Management System (Case Study of Yamus Laundry) - Ayu Latifah; Moch Idham Hanafi (Jurnal Sistem Cerdas, 2026)
Yamus Laundry faces significant operational challenges due to its manual process for recording customer, transaction, and inventory data, which is prone to errors, data loss, and service disruptions. The objective of this research is to design and build a web-based laundry management system to serve as a centralized platform to address these problems. The system was developed using the Rational Unified Process (RUP) method with system modeling based on the Unified Modeling Language (UML), and it was implemented using the PHP programming language and the Laravel framework. This research resulted in a functional web application that has successfully passed Black Box testing. The system includes key features such as integrated customer data management, transactions with automatic quota deduction, and an inventory module with low-stock notifications. The implementation of this system has been proven to reduce the risk of recording errors, lighten the staff's workload, and improve data accuracy, allowing all operational activities at Yamus Laundry to run in a more organized and efficient manner.